Report of an eight-year experience with Camille's transarticular technique of cervical spinal stabilization. (January 2022) - Goel, Atul; Biswas, Chandrima; Shah, Abhidha; Rai, Survendra; Dandpat, Saswat; Bhambere, Sagar
Highlights: Camille's transarticular screw fixation technique is strong and reliable. The authors discuss their experience with this technique. Satisfactory arthrodesis was observed in all patients. The technique stabilizes the fulcrum of movements. The facets are strongest parts of the vertebra. Abstract: We present our experience with Camille's cervical transarticular screw fixation technique. During the period June 2012 to April 2020, 2422 screws were implanted in 321 patients by Camille's transarticular cervical spinal screw fixation technique. The indications of screw implantation were radiculopathy/myelopathy related to cervical spondylosis in 258 cases, cervical OPLL in 54 cases and Hirayama disease in 9 cases. The follow-up ranged from 6 to 92 months. In the entire series, there were no nerve or vessel injury or any other intraoperative 'complications' related to screw implantation. There was no instance of screw pull out or screw failure. There was no metal implant related infection. Satisfactory arthrodesis of all the treated spinal segments was observed on investigations done at a minimum follow-up of 6 months. Camille's transarticular screw fixation technique is a relatively simple surgical procedure and provides a safe, strong and reliable arthrodesis at the fulcrum of spinal movements.